KESESUAIAN PELAKSANAAN STANDAR PELAYANAN MINIMAL (SPM) BIDANG FARMASI DI INSTALASI FARMASI RUMAH SAKIT UNDATA PALU - Faradillah, Nurul; Mukaddas, Alwiyah; Diana, Khusnul (Univ. Tadulako, 2017)
This study aims to determine the suitability of the implementation of the Pharmacy Minimum Service Standards in the hospital at pharmacy section that includes: the length of service waiting time of compounded and available drugs, no error incident of drug administration and prescribing in refer to the formulation at the pharmacy installation, outpatient unit, in Undata Hospital, Palu. This study is a descriptive with quantitative data retrieval. Samples were prescription entered at the Undata hospital in the period from February to May 2016 including 12 sheets of cash prescription, 10 sheets of cash compounded prescription, 188 sheets of guarantee prescription and 187 sheets of guarantee compounded prescription. The results showed that the average length of services waiting time of cash prescriptions was 06 minutes 12 seconds, guarantee prescriptions was 07 minutes 01 seconds, cash compounded prescriptions was 17 minutes 02 seconds, guarantee compounded prescriptions was 16 minutes 05, no error incidence of drug administration was 100% and prescribing in refer to the formularium was 66.2%. These were in accordance to the standard of Kepmenkes RI No. 129 year 2008, except for prescribing in refer to the formularium. Therefore, it is suggested for drugs order should follow the hospital formularium